Thoughts on the table: Gesture as a tool for thinking in blind and visually impaired children - Jelec, Anna; Jaworska, Dorota (Yearbook of the Poznan Linguistic Meeting, 2014)
The theory of embodiment (Lakoff and Johnson 2003; Gibbs et al. 2004) explains the origin of meaning by postulating that thought is influenced by sensorimotor experience (Robbins and Aydede 2009). However, the relation between the body, mind and environment is not unidirectional. Not only do we derive information from the world, but we are also able to use it as an extension of the mind through epistemic actions, strategies that minimize the cognitive load by offloading it onto the environment (Kirsh and Maglio 1994). This paper investigates the potential of gesture as epistemic action. 12 blind and severely visually impaired children and young adults, as well as a control group of 7 young adults were interviewed for the purpose of the study. Participants were asked to explain a set of abstract and concrete concepts while their speech and gestures were recorded. If gesture indeed plays a role in reducing the mental load by externalizing thought, more gestures should be produced for concepts that are more difficult to describe (in this case: abstract, intangible concepts). Qualitative data analysis, as well as simple statistical analyses of gesture type, number and gesture per word rates show that abstract concepts do not generate more gestures, but do prompt blind and visually impaired speakers to use simulation gestures. These gestures constitute reenactments of situations associated with a given concept by the respondent. They are also thought to confirm the embodied cognition hypothesis (Hostetter and Alibali 2008). A number of examples demonstrates that abstract concepts in blind children are strongly grounded in their experience of real-world situations. Findings suggest that gesture is not merely a tool for communication, but a way of extending the capabilities of the mind.